1991
DOI: 10.1172/jci115261
|View full text |Cite
|
Sign up to set email alerts
|

Minimally modified low density lipoprotein is biologically active in vivo in mice.

Abstract: Minimally modified low density lipoprotein (MM-LDL), de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(107 citation statements)
references
References 32 publications
6
100
0
1
Order By: Relevance
“…15,17,18 Injection of mm-LDL in animal models indicates that these bioactive effects appear to be maintained in vivo. 18,42 Therefore, it has been suggested that the generation of mm-LDL may be a very important early step in atherogenesis. Recent studies by several investigators have implicated oxidative decomposition products of lipoprotein phospholipids as possible proinflammatory agents responsible for some of the bioactivity of mm-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,18 Injection of mm-LDL in animal models indicates that these bioactive effects appear to be maintained in vivo. 18,42 Therefore, it has been suggested that the generation of mm-LDL may be a very important early step in atherogenesis. Recent studies by several investigators have implicated oxidative decomposition products of lipoprotein phospholipids as possible proinflammatory agents responsible for some of the bioactivity of mm-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander 45 showed that oils used in many restaurants are kept at 180°C for extended time periods, which results in the appearance of oxidized lipids. Thompson et al* 6 also performed oxidized lipid measurements and showed that oils used for deep-frying in restaurants, institutions, and armed services contained large quantities of oxidized lipids. Finally, Yagi et al 47 measured peroxides in 30 kinds of foods and found that the peroxide content could be as high as 600 nmoles/g food.…”
Section: Discussionmentioning
confidence: 99%
“…Chief among these is an ability to stimulate cholesterol engorgement by macrophages (2,3), which are progenitors of lipidladen foam cells found in early atherosclerotic lesions. In addition, oxidized-LDL influences the chemotactic behavior of monocytes and monocyte-derived macrophages (4,5), promotes endothelial cell damage (6,7), and induces potent mediators of cell proliferation, monocyte adherence, and platelet aggregation (8)(9)(10)(11)(12), all of which may contribute to lesion formation and growth.…”
mentioning
confidence: 99%
“…However, if the oxidant stress is sufficiently great or prolonged, these antioxidants are depleted (13)(14)(15)(16) and injury is propagated among LDL lipids with spread to the protein component through reactive lipid breakdown products (6,17). The atherogenic properties of oxidized-LDL are attributed to this extensively altered particle (1)(2)(3)(4)(5)(6)(7)17), although minimal modifications associated with the initial stages of injury also may be important (10)(11)(12).…”
mentioning
confidence: 99%